Sinusoidal obstruction syndrome as a manifestation of acute antibody‐mediated rejection after liver transplantation. Issue 11 (14th June 2021) - Baliellas, Carme; Lladó, Laura; Serrano, Teresa; Gonzalez‐Vilatarsana, Emma; Cachero, Alba; Lopez‐Dominguez, Josefina; Petit, Anna; Fabregat, Joan
Abstract : Antibody‐mediated rejection (AMR) after liver transplantation is uncommon but, when present, manifests as graft dysfunction. We report the case of a 54‐year‐old woman who developed portal hypertension with pleural effusion and ascites secondary to sinusoidal obstruction syndrome (SOS) due to acute AMR following an ABO‐matched liver transplantation for autoimmune cirrhosis and hepatocellular carcinoma. Initial immunosuppression comprised basiliximab, decreasing prednisone, tacrolimus, and mycophenolate mofetil. After 1 month, she presented with the massive pleural effusion, slight ascites, and normal liver tests. After excluding common causes of pleural effusion, we performed a liver biopsy that showed atypical rejection with the involvement of large centrilobular veins partially occluded by marked endotheliitis and lax fibrosis suggestive of SOS. Direct immunofluorescence study of C4d showed diffuse endothelial sinusoidal staining, and de novo donor‐specific anti‐human leukocyte antigen antibodies were detected in his blood. Thus, we diagnosed AMR focused on centrilobular veins and initiated treatment with defibrotide, steroid pulses, and diuretics. However, this was ineffective, and the pleural effusion only resolved when plasmapheresis and intravenous immunoglobulin were started. This case shows that AMR can cause SOS with portal hypertension and present with a pleural effusion, and as such, it should be suspected after excluding other more common causes of effusion. Abstract : After liver transplantation, acute antibody‐mediated rejection leading to sinusoidal obstruction syndrome and clinical presentation of pleural effusion is successfully treated with plasmapheresis plus immunoglobulins.